Perceived usefulness as mediator on relationship between selected factors towards technological pedagogical and content knowledge of female teachers in Saudi Arabia - Aljuaid, Haifa Eidhah A (2022)
Digital technologies are revolutionising teaching and learning practices in schools and universities all over the world. With the advent of the internet and web technologies, there was a crucial need to develop technological pedagogical content knowledge (TPACK) especially for high school teachers; for the purposes of conducting successful online training that meet the ever-increasing demands of flexible teaching needs in distance education. Therefore, there was an essential need to examine the online training satisfaction, technology acceptance and attitude with technological, pedagogical and content knowledge (TPACK). By reviewing the related literature and employing (TPACK and TAM), this study came to investigate the mediating effect of perceived usefulness in the relationship between online training satisfaction, technology acceptance and attitude with technological, pedagogical and content knowledge. The present study was entirely quantitative with a descriptive design. The main instrument used was a questionnaire whose content validity was checked by a panel of experts. A pilot study was conducted on 45 teachers in high schools to assess the reliability of the instruments. The value of Cronbach’s alpha was from 0.812 to 0.992. The sampling technique was proportional stratified random sampling and the sample size was 367 teachers. To analyse the data, descriptive statistics and the Structural Equation Modelling Technique were used. The finding of this study indicated that shows the mean distributions and standard deviation of the responses to the items measured. According to the highest mean belonged to pedagogical content knowledge (M=4.417, SD=0.675) followed by content knowledge (M=4.412, SD=0.779), Pedagogical Knowledge (M= 4.389, SD= 0.663), Technological Pedagogical Knowledge (M= 4.25, SD= 0.798), Technological Content Knowledge (M= 4.235, SD= 0.814), Technological Knowledge (M= 4.13, SD- 0.808) and Technological Pedagogical Content Knowledge (M= 4.088, SD= 0.761), While the lowest level was observed for Technological knowledge in a virtual platform (M=3.763, SD=0.983). Based on these results it can be concluded that all variables had a mean score of more than the midpoint of the scale (3) and close to “4” which indicates that TPACK had a high level among high school teachers. The results indicated that the online training was shown to be the most salient variable relating to TPACK (β= 0.328, P= 0.001), followed by ATT (β= 0.272, P= 0.001), ICT (β= 0.244, P= 0.001), PU (β= 0.225, P= 0.001), and TA (β= 0.159, P= 0.001). The results also revealed ICT was the most salient variable relating to PU (β= 0.384, P= 0.001) followed by OT (β= 0.308, P= 0.001), TA (β= 0.232, P= 0.001), and ATT (β= 0.211, P= 0.001). Finally, the relationships of online training satisfaction, technology acceptance and attitude with technological, pedagogical and content knowledge (TPACK) were found to be mediated by Perceived usefulness. The main contribution of this study has provided new insights into the understanding of the teacher’s level of knowledge in Technology, Pedagogy, and Content in in Saudi Arabia schools.